The ACTN3 R577X polymorphism across three groups of elite male European athletes - Eynon, N.; Ruiz, J. R.; Femia, P.; Pushkarev, V. P.; Cieszczyk, P.; Maciejewska-Karlowska, A.; Sawczuk, M.; Dyatlov, D. A.; Lekontsev, E. V.; Kulikov, L. M.; Birk, R.; Bishop, D. J.; et al. (PLOS ONE, 2012)
The ACTN3 R577X polymorphism (rs1815739) is a strong candidate to influence elite athletic performance. Yet, controversy exists in the literature owing to between-studies differences in the ethnic background and sample size of the cohorts, the latter being usually low, which makes comparisons difficult. In this case:control genetic study we determined the association between elite athletic status and the ACTN3 R577X polymorphism within three cohorts of European Caucasian men, i.e. Spanish, Polish and Russian [633 cases (278 elite endurance and 355 power athletes), and 808 non-athletic controls]. The odds ratio (OR) of a power athlete harbouring the XX versus the RR genotype compared with sedentary controls was 0.54 [95% confidence interval (CI): 0.34-0.48; P = 0.006]. We also observed that the OR of an endurance athlete having the XX versus the RR genotype compared with power athletes was 1.88 (95%CI: 1.07-3.31; P = 0.028). In endurance athletes, the OR of a "world-class" competitor having the XX genotype versus the RR+RX genotype was 3.74 (95%CI: 1.08-12.94; P = 0.038) compared with those of a lower ("national") competition level. No association (P>0.1) was noted between the ACTN3 R577X polymorphism and competition level (world-class versus national-level) in power athletes. Our data provide comprehensive support for the influence of the ACTN3 R577X polymorphism on elite athletic performance.